AN AGENT-BASED SIMULATION OF AN ALTERNATIVE PARKING BAY CHOICE STRATEGY - Lall, Manoj (The South African Journal of Industrial Engineering, 2020)
Trying to find a parking space in a parking lot is a routine activity for most people in our society. However, in managing the sustained growth rate in the number of vehicle users, the demand on such parking facilities is likely to remain under constant pressure. Both the users and the management of parking lots use various strategies in dealing with the requirement for suitable parking facilities. This paper presents a computational model using an agent-based modelling technique to simulate two commonly used strategies applied to choosing a parking spot under various demand and supply conditions. The model is unique in the current literature, as it is specifically designed to evaluate the effectiveness of the strategies. The analysis of the experimental results shows that, in most conditions, accepting the first available parking spot and then walking to the destination performed better than driving as close as possible to the destination and then searching for an available parking spot.